2019
DOI: 10.12659/msm.916142
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of APOBEC3G Polymorphism with Human Papillomavirus (HPV) Persistent Infection and Progression of Cervical Lesions

Abstract: Background: We studied the effect of APOBEC3G on persistent human papillomavirus (HPV) infection and the correlation between APOBEC3G polymorphism and HPV persistent infection and cervical disease progression in Uygur women in China. Material/Methods: From January 2015 to December 2017, we enrolled 529 Uygur ethnic group patients with HPV infection. SIHA cells were transfected with APOBEC3G. Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot analysis were used to detect mRNA and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…It inhibits the transcription and expression of oncogene HPV E6 and upregulates the transcription and expression of oncogene p53 in Siha cells. since there was reported that the higher levels of APOBEC3B are likely to be associated with the higher frequencies of mutations in some cancer types, it is essential to gain a general profile of the main mutations resulting from APOBEC3B cytosine deamination in different cervical cancer lines 62 . Third, contrary to our findings, APOBEC3A expression was previously reported to be lower in cervical cancer tissues than in normal tissues 63 .…”
Section: Discussioncontrasting
confidence: 87%
“…It inhibits the transcription and expression of oncogene HPV E6 and upregulates the transcription and expression of oncogene p53 in Siha cells. since there was reported that the higher levels of APOBEC3B are likely to be associated with the higher frequencies of mutations in some cancer types, it is essential to gain a general profile of the main mutations resulting from APOBEC3B cytosine deamination in different cervical cancer lines 62 . Third, contrary to our findings, APOBEC3A expression was previously reported to be lower in cervical cancer tissues than in normal tissues 63 .…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies have shown that the expression level of APOBECs 3A, 3B, 3C, and 3G is highly expressed in multiple myeloma (24). Furthermore, the mRNA level of APOBEC3G was highly expressed in cervical cancer (25). Moreover, a previous study displayed that the expression of APOBEC3G in the hepatic metastases was noticeably higher than that in the paired primary colon cancer tissues.…”
Section: Discussionmentioning
confidence: 94%
“…The encoded protein has been found to be a specific inhibitor of human immunodeficiency virus‐1 (HIV‐1). It is found in cervical prelesions and implicated in the development of cervical cancer (Sui et al, 2019). It inhibits the transcription and expression of oncogene HPVE6 (Human papillomavirus gene E6) and upregulates the transcription and expression of oncogene TP53.…”
Section: Regulation Of Pb Components By Epigenetic Machinery and Their Role As Biomarkersmentioning
confidence: 99%
“…This belongs to the TET protein (tumor suppressor genes) family, which is found to be highly methylated in gastric cancer (Figure 3; Table 2). Also, overexpression of cytotoxin‐associated gene A (Cag A) significantly decreased the expression of TET protein in gastric patients (Sui et al, 2019; Zhang et al, 2019). APOBEC3G is a P body component (Zheng et al, 2015).…”
Section: Regulation Of Pb Components By Epigenetic Machinery and Their Role As Biomarkersmentioning
confidence: 99%